The Uncoupling Phenomenon: Dissociation Between Albuminuria and Glomerular Filtration Rate in an Advanced Diabetic Kidney Disease Phenotype - Naufal Fathi Ashari; Harnavi Harun; Russilawati; Dinda Aprilia; SM Rezvi (HM Publisher, 2026)
Background: The classical paradigm of diabetic kidney disease (DKD) assumes a synchronous, linear trajectory where increasing albuminuria predicts the decline of glomerular filtration rate (GFR). However, emerging epidemiology suggests these markers may dissociate in advanced disease stages, particularly under modern renoprotective pharmacotherapy. We aimed to investigate this uncoupling phenomenon by evaluating the correlation between urine albumin creatinine ratio (UACR) and estimated GFR (eGFR) in a specific cohort of advanced DKD patients in Indonesia. Methods: We conducted a cross-sectional analytic study from January to November 2025 at Dr. M. Djamil General Hospital Padang, a tertiary referral center. The study population comprised 30 patients with established DKD, predominantly in CKD Stages 3b and 4. The primary outcome was the Spearman rank correlation (r) between UACR and eGFR, reported with 95% Confidence Intervals (CI). An exploratory sub-analysis compared trends in patients receiving SGLT2 inhibitors (n=12) versus standard care (n=18). Results: The cohort was elderly (mean age 61.93 years) with critical renal reserve depletion (median eGFR 32.50 mL/min/1.73 m²). Median UACR was 403.90 mg/g, yet exhibited massive heterogeneity (IQR: 170.82–1779.27). Spearman analysis revealed a complete lack of linear correlation between albuminuria and filtration function (r = 0.041; 95% CI: -0.322 to 0.395; p = 0.830). While SGLT2 inhibitor users (n=12) demonstrated numerically lower median UACR than non-users (n=18), the dissociation from eGFR persisted in both subgroups. Conclusion: We demonstrate a distinct dissociation between albuminuria severity and filtration function in advanced DKD. This uncoupling suggests that in late-stage nephropathy, structural glomerulosclerosis and tubulointerstitial fibrosis progress independently of permeability changes. Consequently, albuminuria cannot serve as a sole surrogate for disease progression in this phenotype, supporting a dual-biomarker strategy where UACR and eGFR are monitored as independent risk factors.